Effect of premating supplementation with monopropylene glycol on reproductive performance of dairy cows : a field trial : a thesis presented in partial fulfillment of the requirements for the degree of Master of Science in Animal Science at Massey University, Turitea, Palmerston North, New Zealand - Tuñon, Gonzalo Enrique (Massey University, 2005)
Low body condition score (BCS) at calving is associated with extended time to resume cycling in dairy cows. Prolonged postpartum anoestrous intervals (PPAI) are the major source of infertility in New Zealand dairy cows. Postpartum supplementation with monopropylene glycol (MPG), under controlled experimental conditions, was previously shown to reduce PPAI in heifers. This experiment tested this treatment in four large commercial dairy herds. During the 6-week period preceding the planned start of mating (PSM; Week 0), cows were drenched either once (MPGxl) or twice (MPGx2) daily with 200 ml MPG, or served as untreated controls (Con). A total of 2,122 cows were included in the analysis. Analyses were confined to the group of cows that were anoestrus at Week 6 or calved between Week - 6 and Week -4 relative to PSM (n = 684 to 714 per treatment). None of the four variables: oestrous behaviour during the treatment period, anoestrous rate one week before PSM, 3-week submission rate or 3-week pregnancy rate were affected by MPG. However, MPG did increase the 6-week and final pregnancy rates (P<0.005). with MPGxl having higher values (74.6% and 92.1%) than MPGx2 (69.1 and 88.5%) and Controls (67.7% and 88.1%), respectively. MPG-treated cows also produced more milk protein than the control-cows, by 0.01 and 0.017 kg of milk protein per day for MPGxl and MPGx2, respectively (P = 0.02), evidence of a metabolic effect of MPG. Recent studies suggest that diets that are optimal for follicle growth are not necessarily optimal for oocyte quality and subsequent embryo survival. It is hypothesised that MPGxl had positive effects on the follicle/oocyte through gonadotrophin-independent mechanisms and that MPGx2 had negative effects on the embryo. Probably the gonadotrophin-dependent effects necessary for ovulation could not be exerted in the present study because MPG was not administered for sufficient time to effect the LH surge. Both change in body condition score between Week - 6 and Week - 1, and proportion of cows that were anoestrus at Week -1, were influenced by herd, age and time of calving (P<0.05) but not by treatment (P>0.1). Treatment did not influence the proportion of anoestrous cows, treated with progesterone, which were inseminated after oestrus detection (n = 263). Change in BCS affected both milk yield and pregnancy rates, with cows that gained BCS producing less milk (P = 0.01) but showing higher 6-week pregnancy rates (P<0.05). This study highlighted that key factors influencing the percentage of anoestrus at PSM are cow age, time of calving and management of the herd.
Keywords: Dairy cattle reproduction; Milk yield; Anoestrus; Monopropylene glycol; Calving